2022
DOI: 10.1002/job.2649
|View full text |Cite
|
Sign up to set email alerts
|

Start with why: The transfer of work meaningfulness from leaders to followers and the role of dyadic tenure

Abstract: Leaders are expected to enhance the work meaningfulness of followers, but little insight exists on the role of leaders' own experience of meaningfulness in that process.We propose a leader-follower transfer model of work meaningfulness through visionary leadership, grounded in self-concept-based theory, in which leader-follower dyadic tenure shapes the effects of visionary leadership on followers. Moreover, we suggest that work meaningfulness can enhance followers' goal achievement and reduce turnover intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 105 publications
2
10
0
Order By: Relevance
“…Based on SDT, and combining LMX, a supervisor-subordinate interaction context, this article explores the influence mechanism of supervisor developmental feedback on employees' work meaningfulness from the level of employees' internal psychological needs satisfaction. We further verify and deepen prior research conclusions that the LMX quality (Chaudhary 2021) and supervisors' other management behavior (Kipfelsberger et al 2022) profoundly affect employees' work meaningfulness. The results contribute to the discussion of the role of supervisor developmental feedback in activating employees' work meaningfulness.…”
Section: Theoretical Implicationssupporting
confidence: 76%
“…Based on SDT, and combining LMX, a supervisor-subordinate interaction context, this article explores the influence mechanism of supervisor developmental feedback on employees' work meaningfulness from the level of employees' internal psychological needs satisfaction. We further verify and deepen prior research conclusions that the LMX quality (Chaudhary 2021) and supervisors' other management behavior (Kipfelsberger et al 2022) profoundly affect employees' work meaningfulness. The results contribute to the discussion of the role of supervisor developmental feedback in activating employees' work meaningfulness.…”
Section: Theoretical Implicationssupporting
confidence: 76%
“…As van Knippenberg and Sitkin (2013) noted, such research on the broader construct transformational leadership should not be viewed as direct evidence for the effects of visionary leadership (also see van Knippenberg & Stam, 2014). Moreover, although we acknowledge the contributions of this line of research, including those of the recent study by Kipfelsberger et al (2022), especially with regard to theory development, the measures used in these studies blur the distinction between leader vision communication and follower reactions (e.g., by asking about the extent to which a leader “optimistically” or “enthusiastically” provides a “compelling” or “inspiring” vision). To the best of our knowledge, our study is the first to examine whether “pure” visionary leadership—defined more narrowly by van Knippenberg and Stam (2014) as the communication of a future image for a collective with the intention of persuading others to contribute to its realization—is positively linked to follower meaningfulness and, in turn, negatively related to follower turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, they become strongly committed and attached to their organization and feel obligated to continue their work even when other factors, such as unpleasant coworkers, low pay, or more attractive job alternatives would otherwise motivate them to leave (Tse et al, 2013). Indeed, previous research has shown that meaningfulness reduces follower turnover intentions (Kipfelsberger et al, 2022), and that this association can be explained by increased engagement and commitment (Allan et al, 2019;Arnoux-Nicolas et al, 2016;Clausen & Borg, 2010;Leunissen et al, 2018).…”
Section: The Conditional Indirect Effect Of Leader Work Centrality Vi...mentioning
confidence: 99%
See 2 more Smart Citations